1998
DOI: 10.1180/002646198547611
|View full text |Cite
|
Sign up to set email alerts
|

A new mineral, chrisstanleyite, Ag2Pd3Se4, from Hope's Nose, Torquay, Devon, England

Abstract: Chrisstanleyite, Ag2Pd3Se4, is a new mineral from gold-bearing carbonate veins in Middle Devonian limestones at Hope's Nose, Torquay, Devon, England. It is associated with palladian and argentian gold, fischesserite, clausthalite, eucairite, tiemannite, umangite, a Pd arsenide-antimonide (possibly mertieite II), cerussite, calcite and bromian chlorargyrite. Also present in the assemblage is a phase similar to oosterboschite, and two unknown minerals with the compositions, PdSe2 and HgPd2Se3. Chrisstanleyite oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 5 publications
0
24
0
1
Order By: Relevance
“…1b). It corresponds chemically to the Ag-dominant endmember of the series Ag 2 Pd 3 Se 4 -Cu 2 Pd 3 S 4 , described by Paar et al (1998) as a new mineral species from Hope's Nose, Devon, United Kingdom.…”
Section: Sommairementioning
confidence: 99%
See 1 more Smart Citation
“…1b). It corresponds chemically to the Ag-dominant endmember of the series Ag 2 Pd 3 Se 4 -Cu 2 Pd 3 S 4 , described by Paar et al (1998) as a new mineral species from Hope's Nose, Devon, United Kingdom.…”
Section: Sommairementioning
confidence: 99%
“…During a systematic study of polished sections prepared of material from Předbořice, two further platinumgroup minerals were observed: chrisstanleyite (Paar et al 1998) and yet another palladium-dominant phase, the newly recognized analogue of synthetic PdSbSe. The new Pd-Sb selenide is named after Milota Makovicky (b.…”
Section: Introductionmentioning
confidence: 99%
“…58828'N, long. 3828'W) (Paar et al, 1998 and references therein which describe the mineralization found at Hope's Nose). The mineral name honours Dr Théodore Verbeek (1927À1991) who was the first geoscientist to study the Musonoi Se-bearing lens mineralization (1955À1967) and who, along with Dr R. Oosterbosch, first documented (in internal mining reports) the existence of palladium selenides.…”
Section: Introductionmentioning
confidence: 97%
“…Note that micro-analytical data suggest the empirical formula (Pd,Hg,Pb) 3 Se, raising the question whether there is a compositional series between Se-and As-rich (atheneite) end-members. More importantly, however, a Pd-Hg-Se association is known from Au-Se-bearing hydrothermal veins (Mernagh et al 1994, Paar et al 1998, Nickel 2002, Stanley et al 2002, for which a temperature of formation of about 100°C has been proposed (Simon et al 1997).…”
Section: Se-bearing Phasesmentioning
confidence: 99%